An important new fossil genus of Berothinae (Neuroptera: Berothidae) from Baltic amber - Makarkin, Vladimir N.; Ohl, Michael (Zootaxa, 2015)
Elektroberotha groehni gen. et sp. nov. (Neuroptera: Berothidae) is described from Baltic amber. The genus is assigned to Berothinae based on female terminalia that have the following characteristics: long hypocaudae on gonocoxite 9; sternite 7 that is medially divided into a pair of lateral sclerites; and gonocoxite 8 with a medial process that is very similar to that of some extant berothine genera. The new genus is the first described fossil genus of the subfamily Berothinae. It is noteworthy for the possession of a fully-developed CuP in the hind wing, a vein that is strongly reduced in all other species of the subfamily. The genus Spiroberotha is considered to belong to the Berothinae.